Effect of Zingiber otensii on acute paw-oedema in rats - Hidir, Saadiah Mohd.; Ibrahim, Halijah (Malaysian Journal of Science, 2017)
In the study on glucose oxidase-induced oedema in rats, the aqueous extract of the rhizomes of Zingiber ottensii (Zingiberaceae) did not show anti-inflammatory activity when given intraperitoneally at a dose of 500 mg kg-i it showed slight anti-inflammatory activity at doses of 1 and 2g kg-1. The percentage suppression of oedema at 1 and 2g kg' is about 10% when measured at 2 and 3 hours after the injection of glucose oxidase into the paws. In carrageenin induced oedema, the percentage suppression of oedema at 3 and 4.5 hours after the injection of carrageenin is 60%.